Complete tumor encapsulation on magnetic resonance imaging: A potentially useful imaging biomarker for better survival in solitary large hepatocellular carcinoma. Issue 3 (11th March 2013) - Lu, David S.; Siripongsakun, Surachate; Kyong Lee, Jeong; Wei, Sindy H.; Cheng, Phillip M.; Sabounchi, Saman; Lee, Jong Seok; Raman, Steven; Tong, Myron J.; Busuttil, Ronald W.; Sayre, James
<x xml:space="preserve">Abstract</x> The aim of this study was to determine the prognostic value of complete tumor encapsulation as visualized on magnetic resonance imaging (MRI) in patients with a solitary large hepatocellular carcinoma (HCC) beyond the Milan criteria for liver transplantation (LT). Between December 2000 and March 2011, 57 patients who had a solitary HCC exceeding 5 cm in diameter at the time of initial MRI before any treatment were identified. MRI images of the patients were independently reviewed by 2 experienced readers for the presence of complete tumoral encapsulation. The medical records of the patients were reviewed for an outcome analysis. Thirty of the 57 patients had completely encapsulated HCC according to MRI. There was excellent interobserver agreement between the 2 readers for the assessment of complete encapsulation (κ=0.86). Overall survival was significantly longer for patients with completely encapsulated HCC versus patients with incompletely or nonencapsulated tumors (P<0.001), and this included a subanalysis of 33 patients who received locoregional treatment (LRT; P=0.04). The presence of complete encapsulation was a strong predictor for survival in these patients according to both univariate [hazard ratio (HR)=0.24, 95% confidence interval (CI)=0.12–0.52, P<0.001] and multivariate analyses (HR=0.25, 95% CI=0.07–0.85, P=0.03). The rates of down‐staging (P<0.001) and eventual LT (P=0.02) after LRT were also significantly higher in the patients with completely encapsulated tumors. In conclusion, complete tumor encapsulation on MRI is a potentially useful predictor for favorable biology in patients with a solitary large HCC. This new imaging biomarker may have a role in treatment selection for patients whose tumors exceed the Milan criteria size limits. Liver Transpl 19:283–291, 2013. © 2013 AASLD.